Validation Of A Four Protein Signature For Determining Lymph Node Metastasis And Survival In Oral Squamous Cell Carcinoma In 3 Main Diagnostic Centers In Malaysia. - Fairuz Abdul Rahman; Anand Ramanathan; Lau Shin Hin; George Boey Teik Foo; Sok Ching Cheong; Noor Akmar Nam; Rosnah Mohd Zain (Elsevier Inc., 2024)
Oral Surgery, Oral Medicine, Oral Pathology, Oral Radiology Vol. 128 No. 1 July 2019